Axiological Disintergration of the Social Economy - Nowak , Karolina (Studia Oeconomica Posnaniensia, 2015)
The main objective of the article is to answer the questions as to whether the social economy view of the world is connected with relativism or absolutism from an axiological point of view. The specific perspective of cultural studies was used here which allowed the identification as to how cultural beliefs regulate economic practice. The changes in cultural beliefs are presented with regard to re-definition of truth.